2013
DOI: 10.1371/journal.pone.0053348
|View full text |Cite
|
Sign up to set email alerts
|

Prey Patch Patterns Predict Habitat Use by Top Marine Predators with Diverse Foraging Strategies

Abstract: Spatial coherence between predators and prey has rarely been observed in pelagic marine ecosystems. We used measures of the environment, prey abundance, prey quality, and prey distribution to explain the observed distributions of three co-occurring predator species breeding on islands in the southeastern Bering Sea: black-legged kittiwakes (Rissa tridactyla), thick-billed murres (Uria lomvia), and northern fur seals (Callorhinus ursinus). Predictions of statistical models were tested using movement patterns ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
146
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 186 publications
(156 citation statements)
references
References 72 publications
(83 reference statements)
4
146
0
Order By: Relevance
“…Thus, the field metabolic rate and any other extra energetic demands of bowhead whales in Disko Bay can only be met if the whales feed on much higher copepod densities located in patches, likely near the seabed. Kenney et al [12] suggested that foraging in North Atlantic right whales must occur on dense and discrete layers of zooplankton to meet the energetic requirements, and generally marine predators rely on local patches or clusters of patches of prey rather than on areal average prey densities [13]. This study suggests that bowhead whales spend a considerable amount of time feeding close to the seabed where copepod densities are higher than densities closer to the surface.…”
Section: Resultsmentioning
confidence: 69%
“…Thus, the field metabolic rate and any other extra energetic demands of bowhead whales in Disko Bay can only be met if the whales feed on much higher copepod densities located in patches, likely near the seabed. Kenney et al [12] suggested that foraging in North Atlantic right whales must occur on dense and discrete layers of zooplankton to meet the energetic requirements, and generally marine predators rely on local patches or clusters of patches of prey rather than on areal average prey densities [13]. This study suggests that bowhead whales spend a considerable amount of time feeding close to the seabed where copepod densities are higher than densities closer to the surface.…”
Section: Resultsmentioning
confidence: 69%
“…The overall biomass of PDP and concentration of available energy appears to be higher in the winter seasons, which does not coincide with the higher abundance of dolphins sighted in the summer months. The suitability of prey includes abundance or biomass, as well as the distribution and ease of capture, all of which influence predator distribution (Benoit-Bird et al, 2013) and population size (Benoit-Bird, 2004). However, assessing the quality (i.e., nutritional value) of available prey may be a better indicator for assessing the value of prey for managing cetacean populations.…”
Section: Seasonal Energy Content and Prey Qualitymentioning
confidence: 99%
“…Therefore large foraging areas may be related to better foraging habitat than smaller areas. For example, northern fur seals avoided the smallest prey patches and those separated by large distances, when their foraging paths were compared to aggregations of prey (pollock) (Benoit-Bird et al 2013).…”
Section: Individual Variation In Foraging and Diving Behaviourmentioning
confidence: 99%
“…Firstly, the spatio-temporal resolution of the data is such that foraging areas identified here are likely to constitute hierarchical clusters of foraging patches, rather than individual prey patches (Kotliar & Wiens 1990, Benoit-Bird et al 2013, and the delineation of patches can be sensitive to polygon definition as sumptions. Secondly, since we employed a 2 state SSM behavioural model to utilise data from both position only and TDR tags, resting and foraging locations may not always be differentiated.…”
Section: Individual Variation In Foraging and Diving Behaviourmentioning
confidence: 99%